The costs of transgenerational immune priming for homologous and heterologous infections with different serotypes of dengue virus in Aedes aegypti mosquitoes - Cime-Castillo, Jorge; Vargas, Valeria; Hernández-Tablas, Juan Manuel; Quezada-Ruiz, Edgar; Díaz, Grecia; Lanz-Mendoza, Humberto (Frontiers in Immunology, 2023)
The immune system is a network of molecules, signaling pathways, transcription, and modulation of effectors whose purpose is to control, mitigate, or eradicate agents that may affect the integrity of the host. In mosquitoes, the innate immune system is characterized as highly efficient in combating foreign organisms but with the capacity to tolerate vectorborne diseases. These implications lead to replication, dissemination, and ultimately the transmission of pathogenic organisms when feeding on a host. In recent years, it has been discovered that their innate immune response can trigger an enhanced immunity response to the stimulus of a pathogen that had previously encountered. This phenomenon, called immune priming, is characterized by responding through molecules that prevent the replication of viruses, parasites, or bacteria in their body. It has been documented that immune priming can be stimulated through homologous organisms or molecules, although it has also been documented that closely related pathogens can generate an enhanced immune response to a second stimulus with a related organism. However, the cost involved in this immune response has not been characterized through the transmission of the immunological experience from parents to offspring through Transgenerational Immune Priming (TGIP) in mosquitoes. Here we address the impact on the rates of oviposition, hatching, development, and immune response of Aedes aegypti mosquitoes, whose mothers have been stimulated with dengue virus serotype 2 and/or serotype 4, having found a cost of TGIP on the development time of the progeny of mothers with heterologous infections, with respect to mothers with homologous infections. Our results showed a significant effect on the sex ratio with females being more abundant than males. We found a decrease in